Who Believes in COVID-19 Conspiracy Theories in Croatia? Prevalence and Predictors of Conspiracy Beliefs - Tonković, Mirjana; Dumančić, Francesca; Jelić, Margareta; Čorkalo Biruški, Dinka (Frontiers in Psychology, 2021)
COVID-19 pandemic gave rise to numerous new conspiracy theories related to the virus. The aim of this study was to simultaneously investigate a range of individual predictors of beliefs in COVID-19 conspiracy theories that account for socio-demographic characteristics (age, gender, education, economic standard, the importance of religion and political self-identification), distinctive motivational orientations (social dominance and authoritarianism), relevant social attitudes (sense of political powerlessness and trust in science and scientists) and perceived personal risk (perceived risk for self and family members, concern of being infected and expected influence of pandemic on one’s own economic standard). Participants were 1060 adults recruited from the general public of Croatia. The sample was a probabilistic quota sample with gender, age, level of education, size of a place of living and region of the country as predetermined quotas. The regression model explained 42.2% of the individual differences in beliefs in COVID-19 conspiracy theories. Trust in science and scientists and political powerlessness were the strongest predictors, whereas fear of being infected had the weakest contribution in explaining variance of the criterion. Additionally, results revealed that the relation of authoritarianism with the belief in COVID-19 conspiracies was mediated by trust in science and scientists. The relation between social dominance and belief in conspiracies was also partially mediated by trust in science. Our results suggest that (re)building trust in science and lowering the sense of political helplessness might help in fighting potentially harmful false beliefs about the pandemic.